1995
DOI: 10.1007/bf03165038
|View full text |Cite
|
Sign up to set email alerts
|

Impaired myocardial fatty acid metabolism detected by123I-BMIPP in patients with unstable angina pectoris: Comparison with perfusion imaging by99mTc-sestamibi

Abstract: The present study was undertaken to determine the potential diagnostic value of 123I-BMIPP scintigraphy for the detection of altered myocardial fatty acid metabolism in patients with unstable angina. Both myocardial metabolic imaging with 123I-BMIPP and perfusion imaging with 99mTc-sestamibi were performed at rest in 28 patients with unstable angina in the pain-free state. The regional uptakes of 123I-BMIPP or 99mTc-sestamibi were scored semiquantitatively (0 = normal, 4 = no activity) and compared with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The 1211-BMIPP defects are commonly observed in the area with normal perfusion examined by resting 201 T1 or 99 mTcSestamibi scintigraphy in ischemic heart disease. [7][8][9][10] As reported in the past, most angina patients show signs of the perfusion defect only during chest pain, 27.28 and a few during the pain free period. [27][28][29] Consequently mismatched defects of ' 23 1-BMIPP with normal perfusion is a sensitive marker for detecting abnormal myocardium.…”
Section: Discussionmentioning
confidence: 86%
“…The 1211-BMIPP defects are commonly observed in the area with normal perfusion examined by resting 201 T1 or 99 mTcSestamibi scintigraphy in ischemic heart disease. [7][8][9][10] As reported in the past, most angina patients show signs of the perfusion defect only during chest pain, 27.28 and a few during the pain free period. [27][28][29] Consequently mismatched defects of ' 23 1-BMIPP with normal perfusion is a sensitive marker for detecting abnormal myocardium.…”
Section: Discussionmentioning
confidence: 86%
“…Many clinical studies have also indicated that BMIPP SPECT can identify ischemic myocardium without evidence of myocardial infarction as well as the present study [14][15][16]26,27]. Such decreased myocardial uptakes of BMIPP have been frequently observed in the presence of normal perfusion tracer distribution, and thus metabolic imaging with BMIPP is more sensitive for detecting myocardial ischemia than perfusion imaging in patents with unstable angina.…”
Section: Perfusion/metabolism Dual Spect In Redefined Uamentioning
confidence: 79%
“…In patients with unstable angina, mismatched BMIPP uptake less than thallium has also been observed frequently [66][67][68][69]. Comparison of BMIPP image in 19 patients with unstable angina without prior myocardial infarction and stress thallium scan performed after stabilization of their condition demonstrated that BMIPP decrease was associated with stress perfusion abnormality in 44 of 57 (77%) segments and degree of BMIPP reduction correlated with the degree of perfusion abnormality at stress, degree of wall motion abnormality, and severity of coronary artery stenosis [66].…”
Section: Unstable Angina Pectorismentioning
confidence: 99%